Performance Analysis Factors of Citizens Who Care about AIDS in Semarang City - Nurcahyaningsih, Caturinta; Kasmini, Oktavia Woro; Rahayu, Sri Ratna (Public Health Perspective Journal, 2021)
Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) remain a challenge and public health problem in the world. The biggest obstacle to encounter HIV and AIDS is stigma and discrimination. Citizens Who Care about AIDS (WPA) is a form of community participation in mobilizing the society to be involved in HIV-AIDS prevention and control. Data from the AIDS Prevention Commission (KPA) Semarang City shows that most WPA do not have work programs and have not carried out administrative activities, therefore making it difficult for KPA to conduct monitoring and evaluation. The purpose of this study was to analyze predisposing factors (age, gender, marital status, occupation, educations, level of knowledge, stigma and discrimination), enabling factors (availability of health facilities, support for health services) and reinforcing factors (stakeholder support, regulation, social culture). This study used the Cross Sectional Study method. The research sample consisted of 100 people using the Proportional Stratified Random Sampling technique. The technique of collecting data by interview using a questionnaire. Data analysis was performed using the chi-square test and logistic regression. The results showed that there was an effect of knowledge (p = 0.002), stigma of discrimination (p = 0.000), stakeholder support (p = 0.000), socio-culture (p = 0.016) on WPA performance. The most influential variable is stake holder support (p = 0.000. OR = 3.656). The involvement of stakeholder support is really needed for better WPA performance.